Geometry optimization for proton-exchange membrane fuel cells with sequential quadratic programming method - Xing, Xiu Qing; Lum, Kah Wai; Poh, Hee Joo; Wu, Yan Ling (Journal of power sources, 2009)
Integration between COMSOL Multiphysics™ and MATLAB™ offers a useful option for the self-automated geometry optimization in proton-exchange membrane fuel cells (PEMFCS). It overcomes the difficulties of automatically re-generating high-quality computational meshes and subsequently running the simulations to evaluate the objective function values using commercial software in computational fuel cell dynamics-based designs. Geometry optimization studies of an air-breathing PEMFC searching for the optimum channel ratio at the anode and the optimum open ratio at the cathode, are undertaken. A sequential quadratic programming method is selected to deal with the constrained design problems, while the objective functions are evaluated by running the three-dimensional simulation script of COMSOL™ under the MATLAB™ environment. Simulation results show that for the air-breathing PEM fuel cell operated at 353 K and one standard atmosphere pressure, when the anode channel ratio is fixed at 10%, the optimum cathode open ratios are very similar for the cell operated at voltages of 0.7 and 0.4 V, namely, 49.8% for 0.7 V and 49.5% for 0.4 V. When the cathode open ratio is set at 80% with a cell voltage of 0.7 V, the optimum anode channel ratio is found to be 34.7%.